A Discursive Analysis of the Treatment of English and Indigenous Languages in Post-Colonial Language Policies in Kenya - Makua Maroko, Geoffrey; Samuel Nganga, Chege; Nancy Ong'Onda, Anashia (Universitas Negeri Semarang, 2025)
This article investigates the treatment of English and Indigenous languages in the context of post-colonial language policies in Kenya, utilizing Critical Discourse Analysis as its primary methodological approach. Focusing on the integration of English and Indigenous languages in critical domains such as education, research, and administration, this study unveils a nuanced portrayal of the government's language policy. Four language policy documents were purposively selected. These are the Presidential Working Party on Education and Manpower (Kamunge 1988), the Kenyan Constitution of 2010, The National Curriculum Policy (2018), and The Basic Education Curriculum Framework (2017). Using checklists, key policy recommendations were extracted and analyzed using Fairclough’s Three-Dimensional Model. The study revealed that the underlying hierarchies between English and Indigenous languages embedded in official policy documents. This suggests a paradoxical dynamic which despite the overarching goal of promoting linguistic diversity, biases persist in favor of English. This study recommends a proactive governmental strategy to enhance practical value and benefits awareness of Indigenous languages, advocating their greater exposure and representation in official language policy documents. This approach corresponds with wider initiatives to address historical disparities in post-colonial settings, acknowledging Indigenous languages as essential not only for communication but also as crucial carriers of cultural legacy and identity. It highlights the real benefits of integrating Indigenous languages across various sectors, proposing a definitive approach to a more equitable language policy that genuinely represents Kenya's unique linguistic landscape. This study provides essential insights for politicians and educators to promote inclusive language policies in analogous post-colonial contexts.